Mastery Learning Model based on Appreciation Approach at Photography and Film Program, Universitas Pasundan, Bandung: Basic Photography in Faculty of Art - Reinaldi, Harry (Universitas Pasundan, 2023)
The course’s subjects must contain appreciation dan encourage creativity process from the beginning, because within them exist the value of pedagogic, aesthetic, ethic, sociology, philosophy, morality, even religious. There are problems in learning process of Photography 1 Course, at Fotografi and Film Programme, Faculty of Art and Literature, Pasundan University, Bandung. The problems consists of several factor, such as (1) planning, (2) actualization, (3) learning process, and (4) the obstacles and the supports. This scientific research is held in order to identify the cause of the problems, then to analyze them. The purposes are to (1) developing curriculum, (2) upgrading quality of teacher, and (3) upgrading quality of the learning process in the class itself. This case study research’s design had been chosen to: (1) find the facts about obstacles and the supports of the learning process at Photography 1 Course, from the step of planning until the step of actuating, (2) understanding the problems occurred in teacher’s and student’s side, (3) formulating the conclusion and suggestion for upgrading the quality of the learning process. Data collecting technique was done by (1) study of previous documents, (2) direct observation, (3) interview, and (4) study of the current documents. The data was analyzing by matching, filtering, processing, dan verification. The results of this research are (1) to find some factors which had been became a barrier in order to runs the learning process in Photography 1 course, (2) to find a way and solution to overcome the barrier, and to fulfill the shortcoming, (3) to fix the whole learning process, which include curriculum, learning matters, learning process itself, teacher’s competency, students’ creativity, and also facilities and infrastructure. The result of this research gives suggestion about fixing connected important things between: (1) curriculum, (2) learning process, (3) teacher, (4) students, and of course to encourage preceding research.